How reproducible are kinetic parameter constraints of quartz luminescence? An interlaboratory comparison for the 110 °C TL peak. (March 2018) - Schmidt, Christoph; Friedrich, Johannes; Adamiec, Grzegorz; Chruścińska, Alicja; Fasoli, Mauro; Kreutzer, Sebastian; Martini, Marco; Panzeri, Laura; Polymeris, Georgios S.; Przegiętka, Krzysztof; Valla, Pierre G.; King, Georgina E.; et al.
Abstract: Knowledge of the kinetic parameters E (thermal activation energy) and s (frequency factor) of charge-trapping defects in the quartz crystal lattice is of paramount importance to assessing the thermal stability of associated luminescence signals used for dosimetry and dating. Since methods proposed for constraining thermoluminescence (TL) kinetics usually make use of the signal response to thermal treatments, accurate temperature control is required to obtain valid E and s values. In an attempt to check the extent to which consistent kinetic parameters could be obtained using routine luminescence measurement equipment, we have investigated three methods (isothermal decay, initial rise and the Hoogenstraaten method) in an inter-comparison study involving eight laboratories using Risø and Freiberg Instruments systems. The target signal was the so-called 110 °C TL peak of a sample of Oligocene coastal dune quartz sand from the Fontainebleau sand formation (France). TL glow curves recorded with heating rates in the range 0.02–5 K s −1 showed peak positions varying up to 60 °C between systems at the highest heating rates, attributed to temperature calibration errors and/or thermal lag. Kinetic parameters derived from the complete data set show a large spread, covering the ranges ∼0.5–1.2 eV and 10 6 –10 17 s −1 for E and s . In most cases, interlaboratory variations exceeded those of replicate measurements within individual laboratories. Signal lifetimes at 20 °C derived from the isothermal decay (∼59 min) and initial rise methods (at low heating rates; ∼60–80 min) most closely match the value directly measured at 20 °C from within two luminescence readers (∼70 min). Finally, we discuss the consequences of these findings for dosimetry and dating using luminescence signals and possible ways to reduce systematic errors in laboratory measurements of kinetic parameters. Highlights: Comparison of E and s for the 110 °C TL peak of a reference quartz sample in 8 labs. Three methods were applied: isothermal decay, initial rise, Hoogenstraaten. E and s vary by factors of 2 and 10 11 between labs, lifetimes are consistent. Thermal lag and temperature calibration are probably the main sources of variance.